Teenagers and the experience of fatherhood: a phenomenological approach - Santos Rodrigues, Elisane A. (2003)
This is a qualitative phenomenological study which examines the experience of being a father as lived by teenagers. It was carried out at the Comprehensive Health Assistance Foundation of the Sofia Feldman Hospital. The subjects were teenagers aged between 16 and 20, partners of pregnant girls who went for their antenatal appointments. The data was collected through an open interview, guided by a questionnaire. We report five themes arising from the interviews: expecting the baby was a pleasant experience; becoming more mature through pregnancy; becoming more responsible; taking on the role of father; family as a necessary support; ambivalent feelings. The results of this work help guide assistance to teenage fathers.